Anthologies of Chinese Women’s Poetry Translated into Spanish - Zhimeng, Bai (2023)
The translation of Chinese female poetry into Spanish began in 1929 with Catay: Poemas orientales. During the following years, an increasing number of Spanish versions of poetry written by Chinese women were published. This paper provides a chronological analysis of the anthologies dedicated to the Chinese female poetry. Our main objective is to synthesize the evolution of these compilations and present their different characteristics by periods.